Is a reduction in the individual vigilance of mothers a key evolutionary driver of group formation in white rhinos? - Shrader, A.; Post, J.; Hagenah, N.; Bateman, Bill (Universiteit Stellenbosch * Department of Botany and Zoology, 2013)
A key benefit and evolutionary driver of group living is reduced predation risk. In white rhinos, groups comprise adult females, their calves and one to six unrelated subadults. Subadults benefit from group living through exposure to novel areas, and protection from territorial males (i.e. 'buddy system'). In contrast, it is unclear whether mothers benefit from group living. To determine if they benefit, or if there is simply no cost, we recorded the vigilance of white rhino mothers in different-sized groups. We predicted that as group size increased, calves would have lower predation risk and mothers would reduce their vigilance. In contrast, we found that vigilance did not decrease as group size increased. Our findings thus indicate that decreased vigilance is not a benefit that white rhino mothers gain from living in groups. Also, costs of group formation are minimal for mothers as their large body size and ability to feed on a wide range of grasses reduces competition with other group members. As a result, we suggest that the benefits obtained by subadults, coupled with the lack of costs to adult females, are the main drivers of group formation in white rhinos.